Are Young Consumers Still Susceptible to the Country-of-Origin Effect? - Josiassen , Alexander (Journal of Law and Governance, 2009)
The effect that consumers’ country-related images have on their purchase decisions is known as the country of origin effect. Marketing researchers have thoroughly investigated Country-of-Origin (COO) effects in a range of contexts since the mid-1960s. However, since the 1980s it has been thought (e.g., Levitt 1983; Ohmae 1995) that consumer needs and wants are converging and that nation-states are artificial and superficial entities of little value to consumers indicators of product quality. The argument is that since young consumers are used to seeing products from a variety of countries they do not have the country biases that the COO effect stipulates (Usunier 2006). A recent study (Wong et al. 2008) on young Chinese consumers and the COO effect appears to confirm that young consumers are no longer influenced by the COO effect. The aim of this research was to conceptually investigate how the relationship between young consumers’ product-country image and their product evaluations is influenced by two contextual variables: their product involvement and their perceived product-origin congruency.